From "having a say again" to "back to zero": types of social inclusion in the course of the labour market measure of publicly funded employment - Langer, Philipp (Momentum Quarterly, 2023)
This paper explores the impact of the labor market policy measure of publicly subsidized employment on the social inclusion of the long-term unemployed. Labor market policy in Germany increasingly aims to promote the social inclusion of the unemployed beyond the goals of labor market integration and increasing employability. However, social inclusion is an ambivalent concept that leaves open how and when it can be achieved through labor market policy interventions. On the basis of qualitative interviews with persons in publicly subsidized employment and within the framework of a qualitative longitudinal perspective, three types of social inclusion in the process of a labor market policy measure are elaborated. The article adopts a capability perspective and also asks to what extent the individual's capacity to act have been increased by participation in the employment programme.
Keywords: Labor market policy; long-term unemployment; job guarantee; social inclusion